THERAPEUTICS APPROACHES OF INVERTEBRATE ANIMAL TOXINS: A REVIEW - SHARMA, SIMRAN; UPADHYAY, RAVI KANT (International Journal of Pharmacy and Pharmaceutical Sciences, 2022)
The present review article describes invertebrate venoms and various toxins secreted by them. Animal venoms are stores of novel peptides which exhibit a wide variety of biological effects and actively interact with pathogen and parasites. Animal toxins selectively bind to ion channels and receptors and display show hemolytic, cytolytic, proteolytic, anti-diabetic, antimicrobial and analgesic activity. These generate allergic and inflammatory responses in victims. These disrupt cell membranes and inhibit bacterial growth and kill them. Animal toxins inhibit virus entry into host cells and obstruct virus replication. These were also found highly effective against protozoan and fungal pathogens. By using bioinformatics tools, methods and approaches, both structural and functional diversity of toxin peptides could be harnessed to develop highly effective broad-spectrum drugs for therapeutics. Animal venoms are an inexhaustible source of bioactive molecules, which could be used for the development of immune diagnostics, various pharmaceuticals for therapeutics and bio-insecticides. Present article tries to explore the exceptional specificity and high potency of animal toxins for drug development.